2018
DOI: 10.2135/cropsci2018.03.0184
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Cotton Fiber Development Using Fiber Mutants in the Post‐Genomic Era

Abstract: Cotton (Gossypium spp.) fibers are unicellular trichomes that differentiate from ovule epidermal cells. Cotton fiber development is divided into four distinct yet overlapping stages: initiation, elongation, secondary cell wall (SCW) biosynthesis, and maturation. There are numerous naturally occurring and man‐made fiber mutants that display aberrant phenotypes ranging from fiberless to extremely short fiber, and to immature fiber. These mutants have provided cotton researchers an excellent model system to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…Understanding the fibre development will be crucial for breeding high lint yield and high-quality cotton varieties. Several genes have been identified and verified to be functional in fibre initiation in G. hirsutum and G. barbadense [31]. However, little is currently known about fibre and trichome initiation in G. arboreum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the fibre development will be crucial for breeding high lint yield and high-quality cotton varieties. Several genes have been identified and verified to be functional in fibre initiation in G. hirsutum and G. barbadense [31]. However, little is currently known about fibre and trichome initiation in G. arboreum.…”
Section: Discussionmentioning
confidence: 99%
“…There are several naturally occurring and mutagenesis-induced fuzzless accessions in different cotton species. Previous studies have identified multiple loci controlling the fuzzless trait in tetraploid cottons [22,[29][30][31]. Two of these have been mapped and investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous naturally occurred and human-made fiber mutants that display various fiber phenotypes [7]. These include, among others, fiberless mutant lines MD17, SL1-7-1, and XZ142w [8,9]; seeds with only lint fibers and no fuzz fibers in the naked seed lines N 1 [10] and n 2 [11]; and seeds that are described as extremely short lint fibers in the Ligon lintless-1 (Li 1 ) [12], Ligon lintless-2 (Li 2 ) [13], Li x [14] and li y [4] mutant lines.…”
Section: Introductionmentioning
confidence: 99%
“…The study of cotton fiber development regulation provides not only valuable knowledge to understanding plant cell growth and cell wall biosynthesis, but also candidate genes for cotton molecular breeding [4]. To date a number of genes that function in cotton fiber cells have been identified, including homeodomain transcription factor GaHOX1, GhHOX3 and GhHD1 [5][6][7], bHLH transcription factor GhPRE1 [8], KNOX transcription factor knl1 [9], the sterol carrier gene [10], MYB transcription factors GhMYB25, GhMYB25-like, GhMML3 and GhMML4 [11][12][13][14], NAC transcription factor fsn1 [15], transcription factor WLIM1a gene [16], sucrose synthase gene [17], cotton actin1 gene [18], cotton BURP domain protein GhRDL1 [19], ethylene pathway related genes [20], fasciclin-like arabinogalactan protein, Ghfla1 [21], and TCP transcription factor GhTCP4 [22] etc.…”
Section: Introductionmentioning
confidence: 99%